IMPROVING INTEGRATED SUB-DISTRICT ADMINISTRATIVE SERVICES THROUGH INNOVATION OF POPULATION ADMINISTRATION SERVICES IN JATIBANTENG DISTRICT, SITUBONDO - Agus Sukristyanto; Fadnur Rahman (ABDIMAS, 2022)
In accordance with the Regulation of the Regent of Situbondo Number 35 of 2018 concerning Delegation of Part of the Authority for the Implementation of Licensing and Non-Licensing in Sub-districts within the Situbondo Regency Government and in accordance with the mindset of the real conditions that occur in the community, for the success of the program running in the Jatibanteng District, service solutions were developed. with the aim that people who have met the age requirements of the population have an e-KTP and Family Card through the District Integrated Service system, which functions optimally in serving the needs of the community without exception. With the intention of the community getting more effective, efficient and quality services. Based on the problems and taking into account all the conditions that exist and are experienced in the community, it is very necessary to change the service system by getting closer to the community.